Confucianism and the Taiwan experience - Wu, Li Ching (Taipei : Kwang Hwa Mass Communication)
This program will take you under the skin of modern life in the Republic of China on Taiwan
Editor, Ma Tze Kuo
Keywords: Confucianism -- Taiwan